Socialization of Digital Technology for Children with Special Needs via International Webinar - Chandra Lukita; Suwandi Suwandi; Rifqi Fahrudin; Noor Azura Zakaria; Sudadi Pranata; Yuni Awalaturrohmah Solihah (Universitas Syiah Kuala, 2026)
Children with special needs often face challenges in accessing inclusive and adaptive learning environments, particularly due to limited awareness and utilization of digital technologies among educators and parents. This community service activity aims to enhance understanding and capacity in the use of digital technology to support learning for children with special needs through an international webinar. The program was conducted in Cirebon and involved collaboration with an international expert from Malaysia, targeting educators, parents, and community stakeholders. The method used included a socialization approach delivered through an online webinar platform, featuring presentations, interactive discussions, and question-and-answer sessions. The materials focused on innovative digital tools for early detection, personalized learning, and strengthening collaboration between home and school environments. Evaluation of the activity was carried out through participant feedback and observation of engagement levels during the session. The results indicate that participants showed increased awareness and knowledge regarding the importance and practical use of digital technologies in supporting children with special needs. Participants also expressed positive responses toward the relevance of the materials and the international perspective provided. Furthermore, the activity fostered motivation among educators and parents to adopt digital tools in daily learning practices and encouraged collaboration across stakeholders to create a more inclusive educational environment. In conclusion, the international webinar proved to be an effective approach in disseminating knowledge and promoting the utilization of digital technology for inclusive education in Cirebon, contributing to the empowerment of educators and parents in supporting children with special needs.